Cultural Legacy Speaks Through Walls of Pandoke - Sharif, Saima; Muiz, Khalifa Ahmed; Afza , Rahat (ACADEMIA International Journal for Social Sciences, 2025)
There is an affinity between history and identity. Pakistan stands on unique position in the contemporary world due to its multi-cultural nature. The literary contents of Punjabi language have a magnificent cultural expression which can be perceived in poetic verses of Bulleh Shāh on the walls of Pandoke. This paper deals with the sentiments of natives with ṣūfī poet Bulleh Shāh and his poetry. The essence of his poetry is enlightening the walls and generate a novel strengthen in the form of cultural legacy. The representation of classical poetry on walls is expressing the devotion of residents with sūfī poet Bulleh Shāh and his parents at small town Pandoke. The inscription on walls has socio-cultural values and manifestation from which it is born. This is an unalloyed interpretation of Bulleh Shāh’s poetry which is written on the well, nearby a hub of garbage. When we compare these verses with its environment, this can be creating a sense of symbolical connotation. Along with representation of wall chalking, there is also dynamism of pictorial fabrication in the form of posters on the walls of Pandoke. The social culture of Punjab is known for its generousness and simplicity along with transcending virtuous suggestions.